Game-Based Learning: Increasing the Logical-Mathematical, Naturalistic, and Linguistic Learning Levels of Primary School Students - María Esther Del Moral Pérez; Alba Patricia Guzmán Duque; Laura Carlota Fernández García (Springer, 2018)
Game-based learning is an innovative methodology that takes advantage of the educational potential offered by videogames in general and serious games in particular to boost training processes, thus making it easier for users to achieve motivated learning. The present paper focuses on the description of the Game to Learn Project, which has as its aim not only to promote the use of serious games and digital mini-games for the development of Multiple Intelligences, but also to analyse whether this methodology results in increased learning. Teachers assessed the level achieved by primary education students (N=119) in each learning category, before and after participating in the project, by means of a qualitative instrument. Finally, after corresponding analysis through descriptive statistical techniques, bivariate correlations, and ANOVA, the results showed significant differences between children's learning levels in logical-mathematical, naturalistic and linguistic abilities before and after their participation in this innovative project, thus revealing a widespread increase in every indicator.